(3HQGYI GdEOGQI aj GdTQcGJ GdCeQjcjI (B:s (3OQhS fJYdegG ef GdTQcGJ GdJj JgJe HGdYGedjf aj GdebGe GdChd (B/s - (3hhJQeGf, QhHQJs; (3Mcje(B;(3YdG YHO GdefYe YHO Gdbhis ((3GdbGgQI (B:s (3GdOGQ GdOhdjI ddfTQ h GdJhRjY ,s, 1999)
(3jgOa gPG GdcJGH Gdi HMK GdGSHGH GdQFjSjI hQGA Jahb YOO ef efJLGJgG h NOeGJgG aj cGaI Ohd GdYGde dG JbjOgG GdMOhO Gh GdbjhO GdCSJjQGOjI dCj HdO eKds
Keywords: (3GdhdGjGJ GdeJMOIs; (3OQGSGJ MGdIs; (3GdEOGQIs; (3ecJTaGJ JbfjIs